IMPLEMENTASI MODEL KARAKTER TADZKIROH UNTUK MENINGKATKAN SIKAP RELIGIUS SISWA - Mutaqin, Mumu Zainal (ISLAMIKA, 2022)
The purpose of this research is expected to be able to educate children to become pious and pious children in accordance with Luqmanul's expectations for his children. Tadzkiroh character model to foster and direct to have a good character and prepare to live optimally and beneficial for himself, his family, society, as well as religion and nation. The meaning of tadzkiroh is Show examples, Direct provide guidance, Encourage, provide motivation, Zakiyah, pure, clean, cultivate sincere intentions, Continuity is a habituation process to learn to behave and act, Remind, Repetition repetition, Organize and Heart touch his heart. Implementation of the tadzkiroh character model as an effort to provide knowledge to students. Because school is a place to learn and from there they are taught to have noble qualities such as loyalty, mercy and compassion. Tadzkiroh character building through example and refraction to realize students' religious attitudes through righteous deeds. So that the formation of a person's character will be influenced by the process of imitating, seeing, hearing and following.